Experimental study on the failure mechanism and support optimization of deep soft rock roadway structures for coal mine safety - Zhu, Lingjin; Ma, Fenglin; Yuan, Qiang; Wang, Peng; Zhang, Futao; Su, Guorui; Zhang, Mingtian (Frontiers in Built Environment, 2025)
The effectiveness of roadway support in soft rock under high horizontal stress poses a critical technical challenge in underground engineering. It directly affects mine construction progress and mining safety. In response to support failures, such as significant deformation, sheet wall collapse, and roof fall, encountered during the high horizontal stress soft rock roadway support in coal mines, this study utilizes similar material model experiments to simulate actual roadway excavation processes, aiming to analyze the patterns of displacement, deformation, and failure in the surrounding rock during roadway excavation and assesses the effectiveness of different support methods. Simultaneously, FLAC3D was employed to simulate the working face to obtain the deformation and stress distribution patterns of the surrounding rock in the roadway. Field test verification was conducted using the fiber grating anchor monitoring system to validate the findings. The research findings demonstrate that the novel support design scheme effectively restricts the deformation and stress distribution in the surrounding rock, these research results not only provide a solid scientific foundation for selecting an appropriate support method for the soft rock roadways subjected to high horizontal stress, but also contribute to the enhancement of process safety risk control in coal mining.